Dietary Exposure Among Adults in Selangor, Malaysia, to Heterocyclic Amines and Polycyclic Aromatic Hydrocarbons in Cooked Meat and Fish - Jahurul, Md. Haque Akanda (2010)
Heterocyclic amines (HCAs) and polycyclic aromatic hydrocarbons (PAHs) are possible human carcinogens and potent mutagens which increase the incidence of colon, mammary, prostate, breast and other cancers in rodents. Food containing meat and fish are the most important source of exposure to HCAs and PAHs in the diet and heat-treated foods, especially those which are fried, broiled and grilled. The intake of HCAs and PAHs are influenced by the amount and type of meat and fish ingested, frequency of consumption, cooking methods, cooking temperature and duration of cooking. The aim of the present study was to determine the level of HCAs and PAHs in the most consumed foods in Selangor, Malaysia in order to estimate their exposure to these toxic compounds. The dietary intake of HCAs and PAHs in foods consumed by people in Selangor, Malaysia was determined. Levels of six HCAs, namely: 2-amino-3-methylimidazo[4,5-f]quinoline (IQ), 2-amino-3-4-dimethylimidazo[4,5-f] quinoline (MeIQ), 2-amino-3-8-dimethylimidazo[4,5-f]quinoxaline (MeIQx), 2-amino-3,4,8-trimethylimidazo[4,5-f]quinoxaline (4, 8-DiMeIQx), 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) and 2-amino-3,7,8-trimethylimidazo[4,5f] quinoxaline (7,8-DiMeIQx) and three PAHs, fluoranthene, benzo[b]fluoranthene and benzo[a]pyrene were measured. Forty-two samples of meat and fish were included in the study. High-performance liquid chromatography with photodiode array detector and fluorescence detector was used to analyze HCAs and PAHs, respectively. Dietary food consumption data (g/day), including meat type and cooking method were obtained using food frequency questionnaires, which were completed by 600 randomly selected subjects aged above 18 years. Results of the study showed that the level of total HCAs in food samples studied ranged from 0 to 38.7 ng/g whereas the level of total PAHs was, 0 to 66.28 ng/g. Among the analyzed HCAs and PAHs, PhIP (30.6 ng/g) and fluoranthene (50.96 ng/g) showed the highest level, respectively. The highest level of total HCAs was found in grilled chicken satay (38.7 ng/g) and for PAHs it was in grilled beef satay (66.28 ng/g). The most abundant HCAs such as PhIP and MeIQx, and for PAHs such as fluoranthene were detected in the food products studied. The 4,8-DiMeIQx, 7,8-DiMeIQx (HCAs) for HCAs and benzo[a]pyrene for PAHs were found in 12 and 22% of the meat and fish dishes. The average daily intake level of HCAs was 553.7 ng/capita/day and for PAHs of 297.58 ng/capita/day. The intake of PhIP was the highest, followed by MeIQx and MeIQ, whereas intake of fluoranthene was the highest, followed by benzo[b]fluoranthene and benzo[a]pyrene. The results reveal that grilled and fried meat and fish products were the major contributors to the exposure of HCAs and PAHs